Immunologic, Virologic, and Pharmacologic Characterization of the Female Upper Genital Tract in HIV-Infected Women. (1st April 2015) - Rahangdale, Lisa; De Paris, Kristina; Kashuba, Angela D. M.; Nelson, Julie A. E.; Cottrell, Mackenzie; Sykes, Craig; Emerson, Cindi; Young, Steven L.; Stevens, Trenton; Patterson, Kristine B.; Cohen, Myron S.
Abstract : Abstract: A comparative analysis of cellular and soluble markers of immune activation in HIV-infected women on combination antiretroviral therapy showed that the upper genital tract (UGT) compared to the lower female genital tract was characterized by higher frequencies of potential HIV target cells and increased inflammatory molecules. Despite the activated UGT milieu, HIV RNA could not be detected in paired samples of plasma, cervicovaginal or endometrial lavage. As antiretroviral concentrations were ≥3-fold higher in the endometrium than in the lower genital tract, high antiretroviral penetration and/or metabolism may limit viral replication in the UGT.